Kitab Shahih Bukhari (Kajian Tentang Identitas dan Relevansinya Dengan Fase Kodifikasi Hadis) - Nurcahaya, Nurcahaya (Al-Fikru: Jurnal Ilmiah, 2020)
This study aims to describe the book of Sahih Bukhari and the background of the codification phase of Hadith. This research uses qualitative research methods based on library research (Library Research). Sources of data in this study consisted of primary data sources and secondary data sources. The primary data source in this study is the Sahih Bukhari book written by Imam al-Bukhari, while the secondary data sources are books and journal articles related to the codification phase of hadith. Data analysis used content analysis techniques, namely by deepening the meaning in the literature quotations used. The results showed that the Sahih Bukhari book was the first book compiled containing the Hadiths of the Prophet Muhammad. This book was written in a period of approximately 16 years through a very strict screening process from 600,000 Hadith which resulted in 7,397 Hadiths contained in the book. With regard to the book, the birth of the Hadith codification movement during the era of Imam Bukhari was the dynamics of Islamic law, particularly the influence of Imam Syafi'i. In the period before Imam Syafi'i formulated a system of law making as contained in the ar-Risalah.